Participatory evaluation of information projects, products and services for organisational learning and impact - Alkemade, B.; Batjes-Sinclair, Karen (Technical Centre for Agricultural and Rural Cooperation, 2013)
Published by popular demand and taking feedback from users into consideration, this title serves as a compact primer to the Smart Toolkit for evaluating information projects, products and services (CTA no. 1557). The publication builds on past CTA successes in strengthening the capacities of information professionals to manage their projects, products and services. Aimed at enablers – managers, policy-makers and decision-makers – it provides an invaluable overview of the Smart Toolkit and acts as a quick reference guide, so making the Toolkit that much easier to use.